Proton therapy physics - Paganetti, Harald (Boca Raton Taylor & Francis, 2019)
Proton Therapy Physics provides an in-depth overview of the physics aspects of this radiation therapy modality.
Keywords: Proton beams--Therapeutic use; Medical physics; Cancer--Radiotherapy.